IMPLEMENTASI PERATURAN BUPATI SRAGEN NOMOR 10 TAHUN 2018 TENTANG PETUNJUK PELAKSANAAN PERATURAN DAERAH NOMOR 8 TAHUN 2017 TENTANG PERANGKAT DESA DI DESA JEKAWAL, KECAMATAN TANGEN, KABUPATEN SRAGEN, JAWA TENGAH - Giyanto, Tri (JI@P, 2020)
One of the villages in the Sragen Regency region that conducts village apparatus selection (perdes) is Jekawal Village, which is included in the Tangen District area. The implementation of village apparatus selection (perdes) in Jekawal Village went smoothly, the selection stage was carried out twice, namely mutation selection between village apparatuses with below standard selection results, so that selection was continued from the general public. The selection of village officials (perdes) in Jekawal Village went smoothly according to Sragen Regent Regulation Number 10 of 2018 concerning Guidelines for Implementing Regional Regulation Number 8 of 2017. Implementation of Sragen Regent Regulation Number 10 of 2018 concerning Guidelines for Implementation of Regional Regulation Number 8 of 2017 concerning Jekawal Village Apparatus, Tangen District, Sragen Regency has been going well. The implementation of the policy uses the model of Merilee S. Grindle, namely: 1. Contents of the Policy: 1) Objective: a reference for filling out the Village Apparatus. 2) Change: The process is running optimally. 3) Interests: The interests of the whole community. 4) Benefits: Process is more optimal. 5) Implementer .: Village Apparatus Selection Team. 2. Policy context 1) Power: Strength: (1) Human resources. (2) Facilities and infrastructure. (3) Communication. (4) Technology. Weaknesses: limited operating budget. 2) Strategy: Implement all policies according to regulations. 3. Policy Results: 1) Accuracy of target groups: All members of the village community. 2) Conformity of implementation: In accordance with applicable rules. Factors for the successful implementation of the Edward III model are: 4. Resources: 1) Human Resources (HR): sufficient. 2) Funds: Village income and expenditure budget. 3) Technology: Enough. 4) Facilities / infrastructure: Sufficient. 5. Communication: Dissemination to the RT level. 6. Disposition (implementing attitude): Good attitude, enthusiasm and professionalism. 7. SOP bureaucratic structure: SOP of Jekawal Village Apparatus.